Comparative analysis of PID and neural network controllers for improving starting torque of wound rotor induction motor - Hashmia Sh. Dakheel; Zainab B. Abdulla; Helen Jasim Jawad; Ali Jasim Mohammed (Universitas Ahmad Dahlan, 2020)
Unlike 3-phase squirrel cage induction motor, starting-up of 3-phase wound rotor counter part can be improved by adding an external resistance to the rotor circuit.Thus, leads to reduce starting current and increase starting torque. In this paper two controllers for 3-phase wound rotor induction motor have been proposed include conventional proportional integral derivative (PID) controller and the other based on artificial neural network (NARMA-L2). A comparison between these controllers has been conducted. It has been shown that starting torque of the motor has been improved, when utilizing the neural network controller compared to the conventional counter part. It should be noted that MATLAB/SIMULINK has been used to implement both controllers.